2021
DOI: 10.1002/jmv.27534
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of acute telogen effluvium, a harrowing post‐COVID‐19 manifestation

Abstract: This systematic review focuses on the clinical features, physical examination findings, outcomes, and underlying pathology of acute telogen effluvium (TE), a type of diffuse hair loss, occurring in coronavirus disease 2019 (COVID‐19) recovered patients. MEDLINE/PubMed and Embase databases were queried till October 2021 to identify studies reporting acute TE occurring after COVID‐19 recovery. Data were obtained from 19 studies, which included 465 patients who were diagnosed with acute TE. The median age of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
45
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(76 citation statements)
references
References 33 publications
4
45
1
1
Order By: Relevance
“…These results match those of a meta‐analysis that showed the prevalence of depression, anxiety, and insomnia as 15.97%, 15.15%, and 23.87%, respectively [ 39 ]. Of the study participants, 10.1% reported hair loss similar to those in one study where 24% reported hair loss on average 110.9 days after disease onset [ 40 ].…”
Section: Discussionmentioning
confidence: 73%
“…These results match those of a meta‐analysis that showed the prevalence of depression, anxiety, and insomnia as 15.97%, 15.15%, and 23.87%, respectively [ 39 ]. Of the study participants, 10.1% reported hair loss similar to those in one study where 24% reported hair loss on average 110.9 days after disease onset [ 40 ].…”
Section: Discussionmentioning
confidence: 73%
“…Telogen effluvium (TE) is a type of diffuse hair loss which occurs after COVID-19 recovery. In a study composed of 465 cases diagnosed by hair loss, a mean duration of 74 days from COVID-19 symptom initiation to acute TE was estimated [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to a recent systematic review, patients with post‐COVID‐19 TE have a median age of 44 years, with the predominant dermoscopic findings being decreased hair density, empty follicles and short regrowing hair. 11 The age of our patient deviated considerably from this typical disease picture. While our patient did have empty follicles on dermoscopy, the unprecedented finding of bayonet hair was documented, along with oblique tapered hair fractures.…”
Section: Discussionmentioning
confidence: 55%
“…Recent studies indicate an association between high levels of pro‐inflammatory cytokines (interleukin‐6, interleukin‐1β, interferon, and metalloproteinases 1 and 3) and acute TE. 10 , 11 , 12 Furthermore, the activation of the coagulation cascade secondary to COVID‐19 decreases the concentration of anticoagulant proteins, 13 which may induce the formation of microthrombi that occlude the blood supply of hair follicles. 14 Direct infection of the hair follicle has also been implicated, 15 with an early onset of TE suggesting this mechanism.…”
Section: Discussionmentioning
confidence: 99%